THU0128 Evaluation of Safety, Pharmacokinetics and Pharmacodynamics of BI 638683, A Novel CCR1 Antagonist. (10th June 2014) - Baum, P.; Schoelch, C.; Zimdahl-Gelling, H.; Brown, M.; Webb, D.; Padula, S.; Hilbert, J.; Giessmann, T.; Steffgen, J.
Abstract : Background: Monocytes and macrophages play a major role in the pathogenesis of rheumatoid arthritis (RA). The chemokine receptor CCR1 regulates migration of these cells to synovial tissue and the bone. It is expected that sustained full antagonism of CCR1 will block trafficking of monocytes to the site of inflammation and will block the upregulation of cytokines, adhesion molecules and MMPs to slow the progression of joint damage in RA. Objectives: This clinical study investigated safety, tolerability, pharmacokinetics and pharmacodynamics of the novel selective CCR1 antagonist BI 638683. Methods: In a randomised, blinded, placebo-controlled trial, single rising doses from 1 to 700 mg BI 638683 or placebo were administered to 63 young healthy male volunteers (mean age 32 ± 9 years; mean BMI was 24.7 ± 2.4 kg/m 2 ). Subjects were randomised in a 6:2 ratio to active or placebo per group. Two distinct mechanistic blood-based biomarker assays were used to establish a PK/PD relationship: 1. inhibition of MIP1α-induced CCR1 receptor internalization (RI) and 2. inhibition of RANTES-induced CCR1 dependent gene expression of CCL2, CLEC5A, RAB7B and PPARG Results: All doses of BI 638683 were well tolerated. There were no serious adverse events (AE) and no AEs of severe intensity. There was no dose-relationship of AEs and no difference in the number or category of reported AEs in subjects treated with BI 638683 (7/47; 14.9%) compared to those treated with placebo (3/16; 18.8%). The most frequent AEs were GI disorders which were reported in 5/47 (10.6%) subjects treated with BI 638683 and 2/16 (12.5%) subjects treated with placebo. Only one event of nausea in the 700g mg dose group was rated as drug related. Plasma exposure of BI 638683 increased in a near dose-linear fashion, with a terminal t½ of 5-15 h. Two hours after dosing (the pharmacokinetic tmax ), a dose of 150 mg BI 638683 inhibited RI by approximately 90%. The percentage of inhibition was directly related to the dose of BI 638683. At the 700 mg dose, an 83% inhibition of RI was measured at 24 h after dosing. Maximal inhibition of mRNA expression of the 4 CCR1 dependent marker genes was reached with a dose of 75 mg BI 638683 at the tmax . 24 h after dosing, ≥90% mean inhibition was still maintained for CCL2 and PPARG mRNAs by doses of 300 mg and higher, and for RAB7B mRNA by doses of 500 mg and higher. For CLEC5A, inhibition of 84% and 91% was achieved for the 500 and 700 mg dose, respectively. Conclusions: Treatment with BI 636683 was well tolerated. The biomarker assays indicated substantial inhibition and demonstrated proof of mechanism for BI 638683 as a CCR1 inhibitor in early stage of clinical development, and the PK/PD data using these biomarkers can be used to determine appropriate dosing for this compound. Disclosure of Interest: : P. Baum Employee of: Boehringer-Ingelheim, C. Schoelch Employee of: Boehringer-Ingelheim, H. Zimdahl-Gelling Employee of: Boehringer-Ingelheim, M. Brown Employee of: Boehringer-Ingelheim, D. Webb Employee of: Boehringer-Ingelheim, S. Padula Employee of: Boehringer-Ingelheim, J. Hilbert Employee of: Boehringer-Ingelheim, T. Giessmann Employee of: Boehringer-Ingelheim, J. Steffgen Employee of: Boehringer-Ingelheim DOI: 10.1136/annrheumdis-2014-eular.2352